Olney, Richard John. English Archives: An Historical Survey. Liverpool: Liverpool University Press, 2023. - Stępień, Robert (Archiwa – Kancelarie – Zbiory, 2025)
Recenzja książki: Olney, Richard John. English Archives: An Historical Survey. Liverpool: Liverpool University Press, 2023.